2014
DOI: 10.17576/pengurusan-2014-41-06
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction Among Malaysian Employees: An Application of Spector’s Job Satisfaction Survey in the South East Asian Context

Abstract: Job satisfaction explains individuals' reactions towards their jobs. Many studies find that job satisfaction is a well-known construct that is widely used to study work-related well-being; and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…On the other hand, studies in other countries led to different structure models. In a study in Iranian population, seven factors were identified [ 23 ] in a study on Malaysian employees, eight, four and three factor analysis solutions were reported [ 24 ], in a study in Uganda, a four-factor solution was the best model [ 25 ], while in the Ukraine the best model came out to be a three-facet model [ 14 ]. Concerning the validity of the Greek version, the results of CFA of our study indicated that the nine-factor structural model of the JSS was well-adapted and consistent with the original version of the tool.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies in other countries led to different structure models. In a study in Iranian population, seven factors were identified [ 23 ] in a study on Malaysian employees, eight, four and three factor analysis solutions were reported [ 24 ], in a study in Uganda, a four-factor solution was the best model [ 25 ], while in the Ukraine the best model came out to be a three-facet model [ 14 ]. Concerning the validity of the Greek version, the results of CFA of our study indicated that the nine-factor structural model of the JSS was well-adapted and consistent with the original version of the tool.…”
Section: Discussionmentioning
confidence: 99%
“…Higher scores on the JSS indicate higher levels of job satisfaction. The Malay version has been translated and validated (Chin-Siang et al, 2014;Ibrahim et al, 2014). The reliability of the scale for this study is 0.62.…”
Section: ) Job Satisfaction Survey (Jss)mentioning
confidence: 99%
“…In other words, job satisfaction can be defined as "employees' feelings and ideas about their jobs and workplace" (Rizwan et al, 2016, p. 30). Despite the fact that different experts define job satisfaction differently, many agree that it is crucial for employees' happiness (Daud, 2017;Ibrahim, Dagang, & Bakar, 2014). Because employees spend two-thirds of their time at work, job satisfaction has a big impact on them, whether they are at work or at home (Ibrahim et al, 2014).…”
Section: Related Studiesmentioning
confidence: 99%